2021
DOI: 10.1002/alz.056590
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of plasma and CSF biomarkers across ethnoracial groups in ADNI

Abstract: Background Differences in CSF and plasma Alzheimer’s disease biomarkers between African Americans (AA), Latinos (LA), and non‐Hispanic Whites (NHW) have been reported. The Alzheimer’s Disease Neuroimaging Initiative (ADNI) may offer insights into ethnoracial biomarker differences important for understanding disease trajectory variations among diverse populations. Method We queried the ADNI database for all participants with available plasma pTau181 and NfL (Simoa) and linked CSF biomarkers within 1 year of blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 13 publications
1
23
0
Order By: Relevance
“…Further, a very relevant factor that might affect plasma biomarker levels is ethnicity, which is only beginning to be explored 5 . Studies report contradictory results regarding lower plasma levels of p‐tau in, for example Black or Latin American populations 75–77 . Observed differences may have been dependent on differences in comorbidities, socioeconomic, and educational factors, 76 and whether these factors have different effects at every disease stage is currently unknown.…”
Section: Identify Key Steps Needed To Be Taken Before Widespread Use ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Further, a very relevant factor that might affect plasma biomarker levels is ethnicity, which is only beginning to be explored 5 . Studies report contradictory results regarding lower plasma levels of p‐tau in, for example Black or Latin American populations 75–77 . Observed differences may have been dependent on differences in comorbidities, socioeconomic, and educational factors, 76 and whether these factors have different effects at every disease stage is currently unknown.…”
Section: Identify Key Steps Needed To Be Taken Before Widespread Use ...mentioning
confidence: 99%
“…Studies report contradictory results regarding lower plasma levels of p‐tau in, for example Black or Latin American populations 75–77 . Observed differences may have been dependent on differences in comorbidities, socioeconomic, and educational factors, 76 and whether these factors have different effects at every disease stage is currently unknown. Thus, it is relevant to further study and consider potential confounding factors, such as socioeconomic factors next to other medical factors, for example, kidney function and BMI.…”
Section: Identify Key Steps Needed To Be Taken Before Widespread Use ...mentioning
confidence: 99%
“…A few reports have suggested that plasma biomarker levels and performances tend to differ between participants of different ethnoracial backgrounds [62 ▪▪ ,63 ▪▪ ] whereas another study did not report any differences [64 ▪▪ ]. Importantly, other studies have pointed to a likelihood that the intensity of brain pathological changes appear to be less pronounced in participants of non-European ancestry who also tend to be less affected by the presence of the major genetic risk APOE ε4 [65 ▪▪ ,66].…”
Section: Findings Suggesting That Blood Biomarkers Are Not Ready For ...mentioning
confidence: 96%
“…tested whether there are differences in plasma and CSF biomarkers among participants in the multi-site Alzheimer's Disease Neuroimaging Initiative (ADNI) study when stratified by race and ethnicity, and controlling for factors that included measured sociodemographic variables and history of cardiovascular disease. 7 Considering the role of confounding health conditions, Berry et al…”
Section: E D I T O R I a Lmentioning
confidence: 99%
“…With regard to examining blood biomarkers among diverse research participants, Windon et al. leveraged fluid biomarker data collected in the ADNI study 7 . They examined CSF Aβ42, total tau, and p‐tau181 concentrations and plasma p‐tau181 and NfL concentrations in 47 Black participants matched to 141 Non‐Hispanic White participants and 43 Latino participants matched to 129 Non‐Hispanic White participants.…”
mentioning
confidence: 99%